PATIENTS' UNDERSTANDING OF NURSING INSTRUCTIONS IN CARDIAC CATHETERISM: A QUALITATIVE STUDY - Tatiane Roberta Fernandes Teixeira; Marla Andréia Garcia de Avila; Eliana Mara Braga (Universidade Federal do Paraná, 2019)
Objective: To understand patients' knowledge about the cardiac catheterization procedure in order to elaborate pre-catheterization nursing instructions. Methods: Qualitative study with 31 adult patients from a teaching hospital in the inland of the state of São Paulo, conducted in the first half of 2015. Data was collected through semi-structured interviews and analyzed with the use of Content Analysis. Results: Three categories emerged from the statements, as follows: Understanding of the signs and symptoms that led to the need to perform cardiac catheterization; Partial assimilation of written information received by the patients, and Ignorance of the cardiac catheterization procedure performed. Conclusion: The construction and implementation of adequate planning of health instructions clarifies the doubts of the individuals, so that they are more prepared to make sound decisions regarding their health, and promotes the recognition of nursing actions.